Various methods of Purkinje cells transplantation and their functional response in Lurcher mutant mice - Schmidtmayerová, B; Cendelín, J; Korelusová, I; Vozeh, F (Prague medical report, 2005)
Embryonic cerebellum was transplanted to adult Lurcher mutant mice affected with hereditary olivocerebellar degeneration and with resulting cerebellar ataxia. Grafts were applied as solid pieces of tissue or as cell suspensions. The aim was to replace Purkinje cells lost by the neurodegeneration with embryonic cells and to observe the effect on motor symptoms of cerebellar ataxia. Success rate of the two methods was also compared. Motor skills were tested before and in week intervals after the transplantation. The results were compared with sham-operated controls. When the solid graft was transplanted, the success rate was two times higher as compared with the cell suspension method. Fibre sprouting and cell migration from the graft to the host tissue was observed. Insignificant amelioration of motor skills was found in mice after the solid cerebellar tissue transplantation, while the cell suspension application had no effect.
Keywords: Olivopontocerebellar Atrophies; myši - mutanty neurologické; myši; Cell Transplantation; Animals; Mice; Purkinje Cells; Mice, Neurologic Mutants; transplantace buněk; zvířata; olivopontocerebelární atrofie; Purkyňovy buňky